OPTIMIZING NON-TAX REVENUE AT CLASS III AIRPORTS: A POLICY ANALYSIS - Husnul Muamilah; Ratna Dewi Kusumawati; Mahsun Mahsun; Tia Rahmatika (COMPETITIVE, 2026)
Non-Tax State Revenue (PNBP) is a crucial component in supporting the fiscal sustainability of the airport sector, particularly at Class III airports with limited traffic volume and revenue capacity. An unbalanced revenue structure has the potential to increase fiscal vulnerability to external shocks. This study aims to analyze PNBP management policies and their implications for fiscal resilience at Class III airports. This study uses a qualitative approach through policy analysis with a case study design at Sangia Nibandera Airport. Data were obtained from PNBP realization reports, related regulations, and supporting policy documents, which were analyzed descriptively and analytically. The analysis results show that PNBP realization in 2022 only reached 60.20% of the target. The revenue structure is dominated by passenger-based aeronautical revenue, with Aircraft Passenger Services (PJP2U) contributing 72.20%, while non-aeronautical revenue contributed less than 10%. This dependence increases fiscal vulnerability to fluctuations in passenger numbers and flight frequencies. This study concludes that optimizing PNBP requires strengthening governance, diversifying non-aeronautical revenues, and establishing risk-based targets to improve fiscal resilience.